Utilization of E-Books in E-Library Applications to Improve Digital Literacy of Librarians - Farika, Miatul; Samosir, Fransiska Timoria; Sa’diyah, Lailatus (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
The use of technology in the form of e-library applications, especially e-books, is an important element in increasing digital literacy among educators and students. Utilization of electronic books (E-books) as a user activity in searching for and accessing necessary information through e-library applications. E-book utilization refers to the way users search for the information they need. The aim of this research is to determine the use of e-books in e-library applications in increasing digital literacy of users. This research uses a descriptive analysis method with a qualitative approach. Observation, interviews and documentation as data collection methods. The use of e-books in e-library applications also contributes to increasing ease of access to information and the level of digital literacy for users. Users use e-books to support the learning, work, research and self-development processes. According to the author, the use of e-books at the Muhamadiyah Bengkulu University Library UPT is still less than optimal, the existing collections in the e-library application are still relatively limited or not diverse, this is due to the limited budget of the library unit so that users cannot make maximum use of e-books. So with this, it is hoped that in the future librarians will make every effort to increase the collection of library materials, as well as carry out promotions so that readers can maximize the use of e-books and utilize them effectively.